Malaysian crude oil emulsions:1.physical and chemical characterizations - Zulkania, A.; Pramudono, B.; Mat, Hanapi; Idris, A. K.; Mohd. Manan, M. (Faculty of Chemical and Natural Resources Engineering, UTM, 2001)
Emulsion can become very important in all stages in petroleum recovery and processing industry such as drilling, completion, and production of hydrocarbon reservoir, Knowledge of the characteristics of the crude oil and oilfield brine that contributes to the formation of stable emulsion is therefore important. In this study, both chemical and physicochemical properties of different crude oils and oilfield brines from the East Coast of Malaysia were investigated. The crude oils from six different oilfields have been characterized for density, viscosity, surface tension, and interfacial tension. In most cases, the crude oil emulsions are characterized by high amount of saturated hydrocarbon, a varying amount of waxes (8 -15%), and a low content of asphaltene (0 - 14%). It was found that n-paraffin with carbon number between 6 to 20 are generally content in most of crude oil emulsion samples. There is a correlation between the crude oil emulsion viscosity and the waxes content of the crude oil. It was also obtained that the salinity of Malaysian oilfield brines varies between 9.4 to 20.2 and there is correlation between the salinity of oilfield brine and interfacial tension of crude oil emulsion.